Synergistic Effects of a Tomato chlorosis virus and Tomato yellow leaf curl virus Mixed Infection on Host Tomato Plants and the Whitefly Vector - Li, Jie; Wang, Ji-cheng; Ding, Tian-bo; Chu, Dong (Frontiers in Plant Science, 2021)
In China, Tomato chlorosis virus (ToCV) and Tomato yellow leaf curl virus (TYLCV) are widely present in tomato plants. The epidemiology of these viruses is intimately associated with their vector, the whitefly (Bemisia tabaci MED). However, how a ToCV+TYLCV mixed infection affects viral acquisition by their vector remains unknown. In this study, we examined the growth parameters of tomato seedlings, including disease symptoms and the heights and weights of non-infected, singly infected and mixed-infected tomato plants. Additionally, the spatio-temporal dynamics of the viruses in tomato plants, and the viral acquisition and transmission by B. tabaci MED, were determined. The results demonstrated that: (i) ToCV+TYLCV mixed infections induced tomato disease synergism, resulting in a high disease severity index and decreased stem heights and weights; (ii) as the disease progressed, TYLCV accumulated more in upper leaves of TYLCV-infected tomato plants than in lower leaves, whereas ToCV accumulated less in upper leaves of ToCV-infected tomato plants than in lower leaves; (iii) viral accumulation in ToCV+TYLCV mixed infected plants was greater than in singly infected plants; and (iv) B. tabaci MED appeared to have a greater TYLCV, but a lower ToCV, acquisition rate from mixed-infected plants compared with singly infected plants. However, mixed infections did not affect transmission by whiteflies. Thus, TYLCV+ToCV mixed infections may induce synergistic disease effects in tomato plants.